2012
DOI: 10.1016/j.annals.2012.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of search cost reduction on seasonality

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…Some of them are focused on breaking down the seasonal factors that constitute the time series, i.e., [1,44,45,46,47,48]. Other papers prefer to develop predictions or modeling [49,50,51,52,53,54,55,56,57,58].…”
Section: Methodsmentioning
confidence: 99%
“…Some of them are focused on breaking down the seasonal factors that constitute the time series, i.e., [1,44,45,46,47,48]. Other papers prefer to develop predictions or modeling [49,50,51,52,53,54,55,56,57,58].…”
Section: Methodsmentioning
confidence: 99%
“…A second group of studies (Goh & Law, 2002;Kulendran & Wong, 2005;Lim et al, 2009;Vergori, 2012) departed from a forecasting perspective, whereby they looked at several models for forecasting tourism demand, with a relevant role laid out for seasonality. Another cluster in the tourism literature has looked at seasonality as an impacted or impacting factor (e.g., Lim & McAleer, 2000;Yu et al, 2009Yu et al, , 2010Hadwen et al, 2011;Boffa & Succurro, 2012;Goh, 2012;Pegg et al, 2012). For example, Yu et al (2010) found that the seasonal factor of weather conditions impacted those of demand for two parks in the United States.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most common approach for measuring seasonality is to estimate seasonal factors in time series using deviations proportional to moving averages by means of dummy variables in multi-linear regressions, or other methods based on data series. There are several works based on this approach [17,49,52,[64][65][66][67]. Seasonality is also a key element in tourism forecasting and modeling, which can be considered as a deterministic or stochastic component in a series of analyses [68].…”
Section: Alternatives and Measurement Proposalmentioning
confidence: 99%